'This cold night will turn us all to fools and madmen': Feste, Lear's Fool and the border between 'idiocy' and mental illness. Issue 1 (July 2019) - Equestri, Alice
'Folly' is often used as an umbrella term for Renaissance representations both of 'idiocy' and madness, although early modern legislation and medicine described crucial differences between the two conditions. Shakespeare sometimes stages their liminality by having fools interact with lunatics, as in Twelfth Night and in King Lear . By drawing in particular from socio-legal and scientific ideas of the early modern period, the present article considers some of these interactions to discuss the ways in which fools as intellectually disabled individuals are separated from madmen as mentally ill, while also assessing how occasionally 'idiocy' borders into madness.